Simultaneous surgical treatment for esophagogastric junctional cancer and splenic artery aneurysm resection with spleen preservation using fluorescence imaging: a case report - Mamoru Miyasaka; Yuma Ebihara; Yoshiyuki Yamamura; Kimitaka Tanaka; Yoshitsugu Nakanishi; Toshimichi Asano; Takehiro Noji; Yo Kurashima; Toru Nakamura; Soichi Murakami; Takahiro Tsuchikawa; Keisuke Okamura; et al. (Surgical Case Reports, 2019)
Abstract Background Recently, minimally invasive esophagectomy and gastrectomy for esophagogastric junctional (EGJ) cancer using either thoracoscopy or laparoscopy are frequently performed. In the past decade, minimally invasive surgery with laparoscopy for splenic artery aneurysm (SAA) has also been reported. However, patients with both EGJ cancer and SAA are rare. Case presentation A 66-year-old man, who complained of upper abdominal pain, was found to have esophagogastric junctional (EGJ) tumor. He was diagnosed as having Siewert type II adenocarcinoma. In a computed tomography (CT) scan before surgery, a 10-mm aneurysm in the splenic artery was found. Thus, we performed laparo- and thoracoscopic proximal gastrectomy and lower esophagectomy for EGJ cancer and splenic artery aneurysm (SAA) resection with spleen preservation using fluorescence imaging. We confirmed sufficient blood supply to the spleen after surgery with a postoperative CT scan. The blood supply to the spleen was suspected to be from the great pancreatic artery via the pancreas and from the omental branches of the left gastroepiploic artery via the omental artery. Conclusion Simultaneous surgery for EGJ cancer and SAA is rare due to its potential risk, but evaluation of the blood supply for the spleen by using fluorescence imaging can be useful for this procedure.